The Local Anesthetic Bupivacaine Inhibits the Progression of Non-Small Cell Lung Cancer by Inducing Autophagy Through Akt/mTOR Signaling - Jian-Hua Gu (Frontiers in Oncology, 2021)
Non-small cell lung cancer (NSCLC) is a prevalent malignancy with high mortality and poor prognosis. Bupivacaine serves as a widely used local anesthetic and presents potential anti-tumor activity. Nevertheless, the function of bupivacaine in the NSCLC development remains elusive. Here, we tried to investigate the impact of bupivacaine on the NSCLC progression. Significantly, we revealed that bupivacaine was able to reduce the proliferation and induce the apoptosis of NSCLC cells. Bupivacaine could attenuate the invasion and migration in the cells. Mechanically, the treatment of bupivacaine increased the expression ratio of light chain 3B-II (LC3B-II)/LC3B-I and the expression of Beclin-1 in the NSCLC cells. Meanwhile, the expression of the autophagic adaptor protein p62 was decreased by bupivacaine treatment in the cells. The treatment of bupivacaine attenuated the phosphorylation of AKT and mTOR in the NSCLC cells. The AKT activator SC79 and autophagy inhibitor 3-methyladenine (3-MA) reversed the bupivacaine-inhibited phosphorylation of AKT and mTOR and bupivacaine-induced autophagy, as well as the bupivacaine-attenuated NSCLC progression in the cells. Bupivacaine could inhibit the tumor growth in vivo. In conclusion, we discovered that the local anesthetic bupivacaine inhibited the progression of NSCLC by inducing autophagy through Akt/mTOR signaling. Our finding provides new insights into the mechanism by which bupivacaine attenuates the development of NSCLC. Bupivacaine may serve as a potential anti-tumor candidate for the therapeutic strategy of NSCLC.